Redox Switches Controlling Nitric Oxide Signaling in the Resistance Vasculature and Implications for Blood Pressure Regulation: Mid-Career Award for Research Excellence 2020. Issue 4 (October 2021) - Aramide Modupe Dosunmu-Ogunbi, Atinuke; Galley, Joseph C.; Yuan, Shuai; Schmidt, Heidi M.; Wood, Katherine C.; Straub, Adam C.
Abstract : The arterial resistance vasculature modulates blood pressure and flow to match oxygen delivery to tissue metabolic demand. As such, resistance arteries and arterioles have evolved a series of highly orchestrated cell-cell communication mechanisms between endothelial cells and vascular smooth muscle cells to regulate vascular tone. In response to neurohormonal agonists, release of several intracellular molecules, including nitric oxide, evokes changes in vascular tone. We and others have uncovered novel redox switches in the walls of resistance arteries that govern nitric oxide compartmentalization and diffusion. In this review, we discuss our current understanding of redox switches controlling nitric oxide signaling in endothelial and vascular smooth muscle cells, focusing on new mechanistic insights, physiological and pathophysiological implications, and advances in therapeutic strategies for hypertension and other diseases.